Analisis Trade-Off Theory dan Pecking Order Theory Terhadap Struktur Modal - Wagisuwari, Kadek Saptaria; Sitorus, MM, Dr. Palti MT (Owner : Riset dan Jurnal Akuntansi, 2024)
people hence its liquidity. Through incentive given by the government, property sector in Indonesia is believed to have good performance. Incentives such as subvention for price and VAT are given and supposed to increase purchasing power. The reality is market intentions and incentives provided by the government still do not essentially guarantee a company’s sustainability. Therefore, this study is meant to identify variables that considered to be the most relevant theory in funding decisions of property and real estate companies in Indonesia. This study is descriptive quantitative research using purposive sampling method and utilise 70 observations data that would be processed by panel data regression analysis. It is founded that through trade-off theory, a business risk perspective is considered to have no effect in determining the capital structure. Other perspectives from trade-off theory and pecking theory which are debt tax shield and financial deficit are considered to have positive effect, but firm age has negative effect on determining the capital structure. Through this research, company in property and real estate sector in Indonesia can be considered as a moderate risk taker because their capital structure will be increasing when having benefit from tax or facing financial deficit. They still consider the external factors and tend to fine with the risk and balancing the trade-off between the risk and the benefit of the source of fund